Enhancement of high-order harmonic generation in the presence of noise - YAVUZ, İLHAN; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2011)
We report on our simulations of the generation of high-order harmonics from atoms driven by an intense femtosecond laser field in the presence of noise. We numerically solve the non-perturbative stochastic time-dependent Schrodinger equation and observe how varying noise levels affect the frequency components of the high harmonic spectrum. Our calculations show that when an optimum amount of noise is present in the driving laser field, roughly a factor of 45 net enhancement can be achieved in high-order harmonic yield, especially, around the cut-off region. We observe that, for a relatively weak noise, the enhancement mechanism is sensitive to the carrier-envelope phase. We also investigate the possibility of generating ultra-short intense attosecond pulses by combining the laser field and noise and observe that a roughly four orders of magnitude enhanced isolated attosecond burst can be generated.
Keywords: IONIZATION; PULSES